Aspek Nasionalisme dalam Naskah Drama Penjual Bendera Karya Hermana: Tinjauan Sosiologi Sastra dan Implementasinya Sebagai Bahan Ajar di SMA Negeri 1 Andong - Indriyani, Beti; , Drs. Adyana Sunanda, M.Pd (2016)
The purpose of this study was to (1) describe the structure of drama Script builder penjual bendera by Hermana, (2) the aspect of nationalism drama Penjual Bendera, (3) the implementation of aspects of literary nationalism as teaching materials. This study used a qualitative descriptive approach. The data source of the drama. Data collection techniques using literature techniques, see and record. Mechanical authenticity of the data using triangulation theory. Data were analyzed using the dialectical method. The analysis showed that: (1) the structure of the drama builders Penjual Bendera made up the story themes of the reality of social life that upholds the value of the flag. Facts story: groove in this story using the progressive groove. Figures that Gareng, Sompeng, Jondul, and Barcep. Background spot in the plays that the room center of a house. Background of the night. Aspects of the sad mood (2) aspects of nationalism drama Penjual Bendera consists of: the political, social and economic aspects and the cultural aspects (3) aspects of nationalism in the drama Penjual Bendera by Hermana can be used as teaching materials Indonesian literature in high school. The results are used as teaching materials in the form of handouts. Keywords: aspect of nationalism, sociology of literature, drama penjual bendera, implementation of research results in teaching literature.